Insights on the scale of leptogenesis from neutrino masses and neutrinoless double-beta decay - A. Granelli; K. Hamaguchi; M. E. Ramirez-Quezada; K. Shimada; J. Wada; T. Yokoyama (European Physical Journal C: Particles and Fields)
Abstract We revisit the thermal leptogenesis scenario in the type-I seesaw framework featuring three heavy Majorana neutrinos with a hierarchical mass spectrum. We focus on low energy observables, specifically the lightest neutrino mass $$m_{ν }^{lightest}$$ m ν lightest and the neutrinoless double-beta decay effective mass parameter $$m^{eff}_{β β }$$ m β β eff . In particular, we numerically calculate the minimum mass of the lightest heavy Majorana neutrino, $$M_1^{min}$$ M 1 min , required for successful leptogenesis as a function of $$m_{ν }^{lightest}$$ m ν lightest and $$m_{β β }^{eff}$$ m β β eff , considering both normal and inverted light neutrino mass orderings. Flavour effects are taken into account within the flavoured density matrix formalism. We also examine the interplay between fine-tuned cancellations in the seesaw relation and $$M_1^{min}$$ M 1 min . Recent and forthcoming searches for neutrinoless double-beta decay, along with cosmological probes of the sum of neutrino masses, motivate this analysis, as they can provide key insights into the minimal scale of thermal leptogenesis and its broader implications.